Formative Assessment in the Foreign Language Classroom - Barbosa, Matheus de Almeida; Beserra, Larissa Santos (BELT - Brazilian English Language Teaching Journal, 2015)
The objective of every good teacher is that students can have a successful and progressive performance throughout the course. However, there are times when what is taught in the classroom is not enough for the proper outcome of some students who may have some learning difficulties. "What should we do with these students?", "how can we find the source of their real difficulty?" and "how to deal with such problems?" are common questions among us teachers and about which we wish to reflect in this work. In order to do so, we decided to compare our students with a patient looking for medical care, and the steps we should lead him to overcome the difficults he might face.